Association between hand grip strength and exercise addiction: differences by sport category and sex among elite athletes - Karaoğlu, Barış; Ceviz, Ebru; Ünver, Şaban; Çiftçi, İsa; Demir, Gönül T.; Güvendi, Burcu; Bulgay, Celal; Alpay, Merve; Ihasz, Ferenc; Zoltan, Alföldi; Kovacsik, Rita; Somogyi, Angéla; et al. (Frontiers in Psychology, 2025)
IntroductionHandgrip strength (HGS) is a key indicator of upper-body strength and overall physical fitness. While its links to health and sports performance have been widely studied, its relationship with the risk of exercise addiction (REA) remains unclear. Thus, the present study examines the relationship between HGS and REA across various sports disciplines, sexes, and national contexts, aiming to deepen our understanding of their intricate interplay.MethodsUsing a cross-sectional research design, data were collected from 1,211 high-level athletes from Türkiye (n = 656) and Hungary (n = 555), spanning a wide range of competitive sports. The measures involved demographic questions, the Exercise Addiction Inventory to assess REA, and HGS assessments.ResultsWe found significant negative correlations between HGS and REA among Turkish female athletes competing in racquet and water sports (p < 0.05). In contrast, significant positive correlations emerged in team sports played with hands and target-based sports (p < 0.05). Statistically significant HGS-REA correlations were also observed among Turkish male athletes participating in gymnastics and esthetic sports (p < 0.05). Among Hungarian athletes, a significant HGS-REA correlation was found in male racquet sports athletes and female athletes engaged in combat sports (p < 0.05). Regardless of sports discipline, a statistically significant positive correlation was observed exclusively among Turkish female athletes (p < 0.05).ConclusionThe present study reveals that the correlations between HGS and the risk of REA may vary depending on country, sex, and type of sport. The findings indicate that HGS may be either positively or negatively associated with REA in specific sports disciplines.